Psychosocial changes during COVID-19 lockdown on nursing home residents, their relatives and clinical staff: a prospective observational study - Adriana Catarina De Souza Oliveira; María Gómez Gallego; Carmelo Gómez Martínez; Elena Carrasco Martínez; Jorge Moreno Molina; Juan José Hernández Morante; Paloma Echevarría Pérez (BMC Geriatrics, 2023)
Abstract Background Previous works have observed an increase of depression and other psychological disorders on nursing home residents as a consequence of coronavirus disease 2019 (COVID-19) lockdown; however, there are few studies that have performed a comprehensive evaluation of all people involved in nursing homes environment. The objective of the work was to analyse the impact of lockdown on psychosocial factors of nursing home residents, relatives and clinical staff and how these variables have influenced residents’ survival. Methods A prospective study was designed. Evaluations were performed at three different times: a) at the beginning of Spanish confinement, in March 2020; b) just before the second wave of the pandemic, with relaxation of security measures but in lockdown, and c) in January–February 2021, at the end of the second wave, when visits were already allowed. The study was conducted on three different nursing homes. Three hundred and one residents, 119 clinical staff and 51 relatives took part in the study. Anxiety and depression were evaluated in all participants. A scale on the meaning of suffering was also performed. In addition, burnout status was also determined in the clinical staff. Results All participants showed lower depression during lockdown, while at the beginning and at the end of the confinement, these values were significantly increased. In residents, these changes were dependent of cognitive status (p = 0.012). Anxiety was significantly higher in residents. The evolution of anxiety was similar than with depression, with lower values during confinement, although clinical staff showed higher anxiety levels at the beginning. The feeling of suffering was significantly lower in the clinical staff than in resident and relative groups. Residents’ survival was dependent of cognitive status (p = 0.018) and voluntary confinement (p < 0.001). Conclusions During the first COVID-19 lockdown, psychological wellbeing of residents cared in nursing homes, their relatives and staff did not seem to be seriously affected. Previous mental health in relatives and staff together with a resilient approach to the adversity might partly be protecting factors. The lack of consequences on residents’ anxiety, depression and perception of social support may reflect the special attention and care they received. Finally, as in the current study only data of the first two COVID-19 waves were analysed, its findings might be partly generalized to all the pandemic.